Effect of different durations of overdistention on rat bladder function and morphology - Jin,Xiao-Dong (2012)
We investigated the contribution of the duration of overdistention (DOD) to rat bladder function and morphology and explored its possible molecular mechanisms. Bladder overdistention was induced in male Sprague-Dawley rats (200-250 g) by an infusion of saline. Forty rats were divided into 5 groups submitted to different DOD, i.e., 1, 2, 4, and 8 h, and control. Bladder function was evaluated by cystometry. Morphological changes were observed by light and transmission electron microscopy. Compared to control (44.567 ± 3.472 cmH2O), the maximum detrusor pressure of groups with 2-, 4- and 8-h DOD decreased significantly (means ± SEM): 32.774 ± 3.726, 31.321 ± 2.847, and 29.238 ± 3.724 cmH2O. With the increase of DOD, inflammatory infiltration and impairment of ultrastructure were more obvious in bladder tissue. Compared to control (1.90 ± 0.77), the apoptotic indexes of groups with 1-, 2-, 4-, and 8-h DOD increased significantly (6.47 ± 2.10, 10.66 ± 1.97, 13.91 ± 2.69, and 18.33 ± 3.28%). Compared to control (0.147 ± 0.031/0.234 ± 0.038 caspase 3/β-actin and Bax/Bcl-2 ratios), both caspase 3/β-actin and Bax/Bcl-2 ratios of 1-, 2-, 4-, and 8-h DOD increased significantly (0.292 ± 0.037/0.508 ± 0.174, 0.723 ± 0.173/1.745 ± 0.471, 1.104 ± 0.245/4.000 ± 1.048, and 1.345 ± 0.409/8.398 ± 3.332). DOD plays an important role in impairment of vesical function and structure. With DOD, pro-apoptotic factors increase and anti-apoptotic factors decrease, possibly contributing to the functional deterioration and morphological changes of the bladder.